2004
DOI: 10.1002/lt.20045
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle clamping with ischemic preconditioning in liver resection

Abstract: Hepatic pedicle clamping (HPC) is widely used to control intraoperative bleeding during hepatectomy; intermittent HPC is better tolerated but is associated with blood loss during each period of reperfusion. Recently, it has been shown that ischemic preconditioning (IP) reduces the ischemia-reperfusion damage for up to 30 minutes of continuous clamping in healthy liver. We evaluated the safety of IP for more prolonged periods of continuous clamping in 42 consecutive patients with healthy liver submitted to hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 13 publications
1
72
0
5
Order By: Relevance
“…Therefore, the majority of subjects enrolled in the clinical trials of IPC in LR (Table 3) mirror the nonlethal models of warm ischemia in the laboratory. 20,21,23 Hence, it is not surprising that although IPC decreases RP injury in patients undergoing LR, it does not improve clinical outcomes. Conceptually, although the improvement of even mild to moderate RP injury is likely to translate into improved clinical outcomes, such a small incremental benefit of IPC is hard to demonstrate unless a very large numbers of patients (probably several hundreds) are enrolled.…”
Section: Liver Resectionmentioning
confidence: 99%
“…Therefore, the majority of subjects enrolled in the clinical trials of IPC in LR (Table 3) mirror the nonlethal models of warm ischemia in the laboratory. 20,21,23 Hence, it is not surprising that although IPC decreases RP injury in patients undergoing LR, it does not improve clinical outcomes. Conceptually, although the improvement of even mild to moderate RP injury is likely to translate into improved clinical outcomes, such a small incremental benefit of IPC is hard to demonstrate unless a very large numbers of patients (probably several hundreds) are enrolled.…”
Section: Liver Resectionmentioning
confidence: 99%
“…However, cur rent research has demonstrated that the beneficial effects of IPC on liver regeneration is mediated by up regulating growth- Clavien et al [204] ( 2003) 100 (50) Nuzzo et al [209] ( 2004) 42 ( Chouker et al [206] ( 2004) 68 ( Chouker et al [207] Protective against IRI by attenuating neutrophil activation and IL-8 release…”
Section: Resultsmentioning
confidence: 99%
“…Further human liver resection studies have shown that IPC reduces post-operative serum aminotransferase levels in both steatotic [204] and cirrhotic [205] livers and improves postreperfusion haemodynamic stability [206] (Table 1). Although IPC is protective against IRI [207,208] , it did not influence the morbidity and mortality rates in human studies [204,209,210] . In the transplant setting, Jassem et al [211] reported lower serum aminotransferase levels and shorter intensive care stay in IPC-treated cadaveric donor allografts.…”
Section: Clinical Implications Of Ischaemic Preconditioning In Liver mentioning
confidence: 90%
“…In contrast, there are no differences between the three groups for Hb, platelet count, creatinine, PT, Alb, total protein, AST, T Bil, and LDH. Many studies have used aminotransferase levels to assess the severity of hepatic injury resulting from ischemia [30][31][32]. Although serum AST and ALT levels are currently considered by many clinicians as most sensitive markers reflecting liver ischemic damage they also are influenced by the injury caused by liver transection resulting in much higher levels.…”
Section: Discussionmentioning
confidence: 99%